Fluorocarbon compatibilized gold-silica nanocomposites for recyclable regioselective hydroamination of alkynes in a fluorous biphasic system - Merican, Z. (American Institute of Physics Inc., 2016)
The synthesis and characterization of the mesoporous silica-supported gold (Au@mSiO2) nanoparticles compatibilized with the outer shelled superhydrophobic fluorous (F) "tails" was described. The concept of fluorous biphasic separation was applied in the recycling of the synthesized fluorous material during hydroamination reactions of various alkynes. In the presence of perfluoromethylcyclohexane and heptane as a biphasic liquid system, the F-Au@mSiO2 was found to be a highly active catalyst for hydroamination of various alkynes with anilines, and a near quantitative yield for an imine product and produced a relatively minimal formation of a corresponding hydrolyzed ketone by-product. If perfluoromethylcyclohexane and heptane was used as a biphasic solvent, hydroamination at a lower reaction temperature can also be realized leading to an improved recyclability and conversion. Â© 2016 Author(s).